Employment of a Collagen Conduit Soaked in an Angiogenic Fraction Derived from Natural Latex in the Regeneration of Sciatic Nerve of Rats - Ganga, Marcos VinÍcius Muniz; Fazan, Valéria Paula Sassoli; Coutinho-netto, Joaquim; Catalão, Carlos Henrique Rocha; Bernardino, Camila Araujo; Ferreira Júnior, Rui Seabra [UNESP]; Lopes, Luiza Da Silva (Elsevier, 2013)
Peripheral nerve injuries are very frequent in medical practice and although the use of autografts remains the standard procedure to repair thegap between the proximal and distal stumps, alternative techniques have been proposed to avoid complications to the donor site and speed up the nerve regeneration process. A membrane produced from natural latex has been used successfully both experimentally (angioplasties, esophagus neoformation, reconstruction of the ocular conjunctiva) and clinically (myringoplasties, treatment of skin ulcers), showing angiogenic potential and leading to tissue neoformation. The purpose of this study is to evaluate the capacity of a conduit made with collagen and soaked in an angiogenic protein extracted from látex in accelerating and improving the regeneration after surgically sectioning the rat sciatic nerve. Adult Wistar male rats had the sciatic nerve sectioned under anesthesia with a subtraction of a 10mm nerve fragment. Then they received an autograft implant (inverted nerve fragment) or the interposition into the nerve gap of a tube made up of that collagen and soaked in an angiogenic fraction derived from natural latex. At the endpoint of the experiments, the animals were submitted to neurological function evaluation, and killed by an overdose of anesthesia and exsanguination. The implants (collagen conduit or autograft) and the tibialis and gastrocnemius muscles were removed, fixed and processed with embedding in resin. Cross-section of implants and muscles were per formed and prepared in histological slides to observation under light microscopy. Functional recovery was correlated with histopathological analysis. Both showed a significant better performance in rats that received implants with the collagen conduit soaked in angiogenic fraction derived from natural latex.

Peripheral nerve injuries are very frequent in medical practice and although the use of autografts remains the standard procedure to repair thegap between the proximal and distal stumps, alternative techniques have been proposed to avoid complications to the donor site and speed up the nerve regeneration process. A membrane produced from natural latex has been used successfully both experimentally (angioplasties, esophagus neoformation, reconstruction of the ocular conjunctiva) and clinically (myringoplasties, treatment of skin ulcers), showing angiogenic potential and leading to tissue neoformation. The purpose of this study is to evaluate the capacity of a conduit made with collagen and soaked in an angiogenic protein extracted from látex in accelerating and improving the regeneration after surgically sectioning the rat sciatic nerve. Adult Wistar male rats had the sciatic nerve sectioned under anesthesia with a subtraction of a 10mm nerve fragment. Then they received an autograft implant (inverted nerve fragment) or the interposition into the nerve gap of a tube made up of that collagen and soaked in an angiogenic fraction derived from natural latex. At the endpoint of the experiments, the animals were submitted to neurological function evaluation, and killed by an overdose of anesthesia and exsanguination. The implants (collagen conduit or autograft) and the tibialis and gastrocnemius muscles were removed, fixed and processed with embedding in resin. Cross-section of implants and muscles were per formed and prepared in histological slides to observation under light microscopy. Functional recovery was correlated with histopathological analysis. Both showed a significant better performance in rats that received implants with the collagen conduit soaked in angiogenic fraction derived from natural latex.
Keywords: Sciatic nerve injury; Nerve regeneration; Biomaterials; Angiogenic fraction from natural latex; Hevea brasiliensis